Bioanalysis and Quadrupole-Time of Flight-Mass Spectrometry Driven In Vitro Metabolite Profiling of a New Boronic Acid-Based Anticancer Molecule. (25th August 2020) - Zagade, Aarati Dilip; Shard, Amit; Shinde, Shital; Sahu, Amit Kumar; Sengupta, Pinaki
Abstract: ( E/Z )-(4-(3-(2-((4-chlorophenyl)amino)-4-(dimethylamino)thiazol-5-yl)-2-(ethoxy carbonyl)-3-oxoprop-1-en-1-yl)phenyl) boronic acid, a newly developed molecule having anticancer activity serves as a potential candidate for the further drug development process. In this study, to ascertain the anticancer potential of the molecule, we screened it against different cell lines and compared the activity against the standard drug doxorubicin. The molecule showed promising activity at a low concentration against almost all cell lines used in the study. Apart from that, the molecule was characterized for its pKa and a precise reverse phase high-performance liquid chromatography bioanalytical method has been developed. The method was validated according to the United States of Food and Drug Administration bioanalytical guideline and was found to produce linear response over the calibration range of 0.8–25 μg/mL. Inter- and intra-day accuracy were found to be in the range of 93.44–99.74%, whereas precision [% coefficient of variation (CV)] for inter- and intra-day was ranged between 1.63 and 5.79%, and 0.87 and 6.96%, respectively. The bioanalytical stability testing was carried out in different conditions including 8 h benchtop, 12 h autosampler and three freeze–thaw cycles. The analyte was stable in all the tested stability conditions. Finally, an in vitro metabolite identification study was conducted using quadrupole-time of flight-mass spectrometer, and two metabolites have been identified.